Women Leadership and Organizational Sustainability: A Systematic Literature Review of ESG and Green Innovation - Erna Rusnani; Laila Refiana Said (Journal of Economics Education and Entrepreneurship, 2026)
The increasing global emphasis on sustainability has encouraged organizations to adopt responsible business strategies that integrate environmental, social, and governance (ESG) principles and environmentally oriented innovation. In this context, leadership plays a crucial role in shaping organizational strategies and sustainability practices. This study aims to examine the relationship between women's leadership, ESG governance, green innovation, and organizational sustainability through a systematic literature review. The research adopts the PRISMA framework to ensure a transparent and structured literature selection process. Data were collected from three major academic databases—Scopus, ScienceDirect, and Emerald Insight, covering publications from 2021 to 2026. The initial search identified 168 articles, and after the screening and eligibility process, 32 articles met the inclusion criteria and were selected for the final analysis. The findings indicate that research on women's leadership and sustainability has increased significantly in recent years. The literature consistently shows that female leaders contribute positively to ESG performance by promoting transparency, ethical decision-making, and stakeholder-oriented governance. In addition, women's leadership encourages the development of green innovation, including environmentally friendly technologies and sustainable product development. The study proposes a conceptual model suggesting that women's leadership strengthens ESG governance, which subsequently promotes green innovation and ultimately supports organizational sustainability. These findings highlight the strategic role of gender diversity in leadership in advancing sustainable organizational practices.